Identification of Factors Affecting the Employability of Information Technology Graduates (Global Journal of Management and Business Research, 2021)
Graduate employability has been a typical subject among analysts, governments and advanced education frameworks around the globe uniquely in Sri Lanka but also in the world. In any case, while there is a ton of data and various models that advise on graduate employability, Specially what are the weak areas in the current education framework in universities (State and non state) the system change necessarily according to the industry requirements has been constrained exact research around there. Besides, most employability considers have been led in the Sri Lanka and different pieces of the world, In spite of Information Technology (IT) being one of the most looked for after capability by Sri Lankans, regardless it stays indistinct with respect to why numerous IT graduates battle to verify occupations after graduation.